1985
DOI: 10.1007/bf02148693
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anaerobic bacteria in blood cultures by lysis filtration

Abstract: An anaerobic adaptation of the lysis-filtration system for detection of anaerobic microorganisms in blood is described. The method was compared with a conventional broth bottle system in detection of anaerobic bacteremia after oral surgery. Of 43 blood samples obtained during and after surgery, 31 were positive with the lysis-filtration system and 17 were positive with the broth bottle system. Sixteen aerobic and 62 anaerobic strains were isolated with the lysis-filtration system versus 9 aerobic and 22 anaero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 6 publications
4
22
0
Order By: Relevance
“…The nature of the organisms are typical of those obtained from odontogenic bacteraemia. 13,14 The bacteraemia rate in the cardiac group is similar to that from other studies where antibiotic prophylaxis was administered orally, either in children, or adults. 14,15 This is surprising considering that IV antibiotics should achieve very high blood levels at the time of dental treatment.…”
Section: Discussionsupporting
confidence: 79%
“…The nature of the organisms are typical of those obtained from odontogenic bacteraemia. 13,14 The bacteraemia rate in the cardiac group is similar to that from other studies where antibiotic prophylaxis was administered orally, either in children, or adults. 14,15 This is surprising considering that IV antibiotics should achieve very high blood levels at the time of dental treatment.…”
Section: Discussionsupporting
confidence: 79%
“…The ability of LyF to estimate the intensity of bacteremia was confirmed with values ranging from 1 to 28 CFU/ml following the extraction of a single tooth. This compares well with the data for intensity in adults, for which the values were up to 43 CFU/ml (16), a mean of 3.8 CFU/ml (14), and a mean of 21 CFU/ml (17), respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Preliminary work has shown that the technique of lysis filtration (LyF) appears to be an effective method of estimating the intensity of bacteremia following dental extractions in adults (14,15). There are no data available on the use of LyF with children.…”
mentioning
confidence: 99%
“…Vacuum filtration was done using a 0.45-µm pore-size filter system (Millipore Corp, Billerica, La., USA). This system has been evaluated for aerobic [10] and anaerobic bacteria [11]. After filtration, the filters were placed onto brain-heart infusion agar (Difco Laboratories, Detroit, Mich., USA) plates supplemented with 5% horse blood for anaerobic incubation at 37°C for up to 10 days, before the samples were judged negative.…”
Section: Methodsmentioning
confidence: 99%